Los flujos de capital extranjero en el Ecuador: Uso, destino y consecuencias - Arteta, Gustavo (2000)
The purpose of this paper is to investigate thu destiny and the ctftots vt tho capital inflows in Ecuador and to take note tor the future, because the use or the destiny of the foreign capital in an economy has different economic consequences as well as implications in the design and applications of the policies. In this study we found that the period of capital inflows in form of external private indebtedness. major direct investment and deposits in the financial system, was associated with a deterioration in the private sector balance, the reserves accumulation, and a credit and consumption boom. The high capital mobility in the Ecuadorian economy, estimated through the offset coefficient, suggests the existence of a reduced margin to sterilize the exchange effect of the capital flows. An issue of the research agenda is to analyze the link between the credit expansion caused by the foreign capital and the financial crisis. In special, we need to explain how the moral hazard induced by the economic boom lead then to the crisis.